2019
DOI: 10.1002/art.40906
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes Determined by Cluster Analysis and Their Survival in the Prospective European Scleroderma Trials and Research Cohort of Patients With Systemic Sclerosis

Abstract: Objective Systemic sclerosis (SSc) is a heterogeneous connective tissue disease that is typically subdivided into limited cutaneous SSc (lcSSc) and diffuse cutaneous SSc (dcSSc) depending on the extent of skin involvement. This subclassification may not capture the entire variability of clinical phenotypes. The European Scleroderma Trials and Research (EUSTAR) database includes data on a prospective cohort of SSc patients from 122 European referral centers. This study was undertaken to perform a cluster analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
63
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 40 publications
5
63
0
4
Order By: Relevance
“…In our study, patients with ATA were present in all five trajectory classes while we noted that lcSSc patients were predominantly in class 1 and those with dcSSc were mainly in classes 2 to 5. This heterogeneity is well known and has been confirmed by several recent works highlighting the importance of autoantibodies, cutaneous subset, and disease duration to predict organ complications and survival [7,23,28]. In particular, it appears relevant to distinguish especially ATA-associated lcSSc from ATAassociated dcSSc [33,34].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In our study, patients with ATA were present in all five trajectory classes while we noted that lcSSc patients were predominantly in class 1 and those with dcSSc were mainly in classes 2 to 5. This heterogeneity is well known and has been confirmed by several recent works highlighting the importance of autoantibodies, cutaneous subset, and disease duration to predict organ complications and survival [7,23,28]. In particular, it appears relevant to distinguish especially ATA-associated lcSSc from ATAassociated dcSSc [33,34].…”
Section: Discussionmentioning
confidence: 66%
“…Most patients with ACA (95%) were assigned to class 1. However, 42% of patients in class 1 had ATA, which is a higher proportion than that usually observed in lcSSc [24,27,28]. In addition to lcSSc, there were 20 patients (17%) with dcSSc associated with ATA and whose median baseline mRSS was 9 (IQR 6.5; 9.5).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, Gemma Lepri and Michael Hughes contributed equally to this work. recent work which included 11,318 patients from the EUSTAR database using cluster analysis found that restricting subsets to only skin involvement did not capture the heterogeneity of SSc and that organ damage/autoantibody status identified homogenous groups of patients with different prognosis [17].…”
mentioning
confidence: 99%
“…To date, a total of four subsets have been recognized and validated by multiple studies [20][21][22]: the fibroproliferative, the inflammatory, the limited, and the normal-like subset. The fibroproliferative subset is characterized by a significant proliferative signature (mitotic cell cycle, chromosome segregation, cell division, and microtubule cytoskeleton) and the plateletderived growth factor (PDGF) pathway has been suggested to have a relationship with this subset [17]. In the inflammatory intrinsic subset, the gene expression signature is addressing the immune system process, the inflammatory and defense response, and the vascular response.…”
mentioning
confidence: 99%